2021
DOI: 10.3389/fimmu.2021.617251
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Dengue Envelope Protein Domain III Induces Nlrp3 Inflammasome-Dependent Endothelial Dysfunction and Hemorrhage in Mice

Abstract: Typically occurring during secondary dengue virus (DENV) infections, dengue hemorrhagic fever (DHF) causes abnormal immune responses, as well as endothelial vascular dysfunction, for which the responsible viral factor remains unclear. During peak viremia, the plasma levels of virion-associated envelope protein domain III (EIII) increases to a point at which cell death is sufficiently induced in megakaryocytes in vitro. Thus, EIII may constitute a virulence factor for endothelial damage. In this study, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 85 publications
2
61
0
Order By: Relevance
“…However, data obtained in this present study suggested that virion-surface EIII is a candidate virulence factor that contributes to dengue-elicited thrombocytopenia. In addition, similar to soluble NS1, virion-surface EIII is a virulence factor that contributes to the first-hit in our two-hit DHF model ( 13 , 16 ).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…However, data obtained in this present study suggested that virion-surface EIII is a candidate virulence factor that contributes to dengue-elicited thrombocytopenia. In addition, similar to soluble NS1, virion-surface EIII is a virulence factor that contributes to the first-hit in our two-hit DHF model ( 13 , 16 ).…”
Section: Discussionmentioning
confidence: 93%
“…Here we found that in agreement with platelet activation data ( Figures 1 and S3 – S5 ), treatments with DENV and rEIII induced platelet cell death in a dose-dependent manner ( Figure 3A ). Various cell death inducers, including nigericin (pyroptosis), doxorubicin (apoptosis), rapamycin (autophagy), TNF- α (necroptosis), and erastin (ferroptosis) roughly induced the respective cell death pathway of tested platelets ( Figure 3B , RCD % of total cells; 3C, RCD % of total dead cells; Figure S9 , flow cytometry gating and calculations) ( 13 , 14 ). Intriguingly, when compared with these cell-death agonists, treatments with DENV and rEIII induced considerable pyroptosis, necroptosis, and ferroptosis responses of platelets but only minor levels of apoptosis ( Figures 3B, C ) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations